User damages and the limits of compensatory reasoning - SEE, Alvin W. L. (Institutional Knowledge at Singapore Management University, 2018)
The use of the term “user damages” in reference to compensatory damages is particularly problematic because it tends to overgeneralise the cases and conceal the importance of identifying the relevant loss in each case, which has implications on issues of proof, quantification and mitigation. This has contributed to the persistent neglect to squarely address issues of loss, which has in turn led to both over- and underestimation of the limits of compensatory damages. Once we look past the broad label, it becomes obvious that the cases purportedly unified by a common measure of loss tend to vary widely in facts and that the employment of the same measure was often merely coincidental. If the broad label adds nothing but distraction and confusion, perhaps it is time to consider dropping it from our legal vocabulary.